Down-regulation of Shadoo in prion infections traces a pre-clinical event inversely related to PrP(Sc) accumulation. - David Westaway; Sacha Genovesi; Nathalie Daude; Rebecca Brown; Agnes Lau; Inyoul Lee; Charles E Mays; Janaky Coomaraswamy; Brenda Canine; Rose Pitstick; Allen Herbst; Jing Yang; et al. (PLoS Pathogens)
During prion infections of the central nervous system (CNS) the cellular prion protein, PrP(C), is templated to a conformationally distinct form, PrP(Sc). Recent studies have demonstrated that the Sprn gene encodes a GPI-linked glycoprotein Shadoo (Sho), which localizes to a similar membrane environment as PrP(C) and is reduced in the brains of rodents with terminal prion disease. Here, analyses of prion-infected mice revealed that down-regulation of Sho protein was not related to Sprn mRNA abundance at any stage in prion infection. Down-regulation was robust upon propagation of a variety of prion strains in Prnp(a) and Prnp(b) mice, with the exception of the mouse-adapted BSE strain 301 V. In addition, Sho encoded by a TgSprn transgene was down-regulated to the same extent as endogenous Sho. Reduced Sho levels were not seen in a tauopathy, in chemically induced spongiform degeneration or in transgenic mice expressing the extracellular ADan amyloid peptide of familial Danish dementia. Insofar as prion-infected Prnp hemizygous mice exhibited accumulation of PrP(Sc) and down-regulation of Sho hundreds of days prior to onset of neurologic symptoms, Sho depletion can be excluded as an important trigger for clinical disease or as a simple consequence of neuronal damage. These studies instead define a disease-specific effect, and we hypothesize that membrane-associated Sho comprises a bystander substrate for processes degrading PrP(Sc). Thus, while protease-resistant PrP detected by in vitro digestion allows post mortem diagnosis, decreased levels of endogenous Sho may trace an early response to PrP(Sc) accumulation that operates in the CNS in vivo. This cellular response may offer new insights into the homeostatic mechanisms involved in detection and clearance of the misfolded proteins that drive prion disease pathogenesis.